Write to shoot : writing short films for production - Beker, Marilyn (Routledge, Taylor & Francis Group, 2017)
"Write to Shoot teaches budding screenwriters and screenwriting filmmakers how to write a short script with production in mind. Beker instructs them how to showcase their strengths, tailor projects to shoestring budgets, resources, and practical production parameters without sacrificing the quality and punch of their screenplays, whether they're creating a sizzle short for an unproduced feature script, an independent creative work, or a soapbox to promote a cause. Write to Shoot: Writing Short Films for Production is a must-have guide for anyone who wants to be sure there will be no surprises on set that come from a script that's not ready for production"--Provided by publisher